CHALLENGES WITH ONLINE TEACHING AMONG LECTURERS DURING A PANDEMIC LOCKDOWN - Rasika Lawrence; Uma Devi; Zahid Saaed; Haslinda Abdullah, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The teaching and learning system is currently witnessing a complete tremendous shift from face-to-face teaching to online teaching due to a pandemic lockdown that is taking place globally lately. The entire education sector has shifted its teaching and learning to an online mode. While all educational institutions and schools are closed due to the movement control order (MCO), teachers remain accountable for the education of their students to be continued at home. Online teaching has been welcomed highly during this pandemic lockdown whereby it is expected to provide learners with a more self-directed and independent learning experience which is very much required in a highly competitive technology arena. However, despite its acceptance in the education industry, the online teaching approach is not without its challenges. This paper aims to discuss the challenges faced by the lecturers in implementing online teaching during a pandemic lockdown in a private higher education institution in Malaysia. Lectures are selected for data collection purposes for this study. Data was collected through interviews and observations. The findings of this study found that the factors like technology, student-factors, student-lecturer relationship, pre-teaching workload, lecturer’s motivation, workspace and facilities, home responsibilities and institutional support have an impact on a lecturer’s work performance and work commitment. This study provides a detailed insight into the challenges of online teaching to the Ministry of Higher Education in Malaysia and the academics so that strategies for overcoming the challenges of online teaching can be developed.